Enhanced anti‐microbial activity in green concrete specimens containing fly ash, nanophase modifiers, and corrosion inhibitor. Issue 4 (29th November 2018) - Harilal, Manu; Uthaman, Sudha; George, R.P.; Anandkumar, B.; Thinaharan, C.; Philip, John; Kamachi Mudali, U.
Abstract : This study reports the anti‐bacterial properties of green concrete containing fly ash, nanoparticle modifiers, and a corrosion inhibitor. Four different concrete specimens, namely control concrete containing ordinary portland cement (CC), fly ash concrete containing 40 wt % fly ash (CF), modified fly ash concrete containing nano‐TiO2 and nano‐CaCO3 (1 wt % each) called CFN, and CFN with 2 wt % corrosion inhibitor (CFNI) are used in the present study. Among the four specimens exposed to microbial culture, CFNI showed minimal bacterial attachment and biofilm density, which is further corroborated from Epifluorescence microscopy and 3D confocal laser scanning microscopy. The CFNI specimens showed the least pH reduction among the four, which resulted in the enhanced microbial resistance. The results unambiguously confirm the synergetic effects of nanophase modifiers and NaNO2 based inhibitor in controlling microbial activity in concrete specimens. The results have promising applications in formulating concrete structures that are exposed to harsh environmental conditions. © 2018 American Institute of Chemical Engineers Environ Prog, 38:e13102, 2019